Influence of curcumin and carbazole on ovine ovarian preantral follicle and granulosa cell functions - B, SAMPATH KUMAR; NANDI, S; GUPTA, P S P; MONDAL, S; V, GIRISH KUMAR (The Indian Journal of Animal Sciences, 2021)
The present study was undertaken to study the effect of plant bioactive compounds curcumin and carbazole on sheep ovarian functions. In the present study, both the bioactive compounds were tested at different levels (Control, T1-1 μM, T2-5 μM, T3-10 μM, T4- 25 μM, T5- 50μM, T6-100 μM) on preantral follicle (PF) growth rate, survival rate (6 days culture), granulosa cell (GC) number increment (2 days culture) and estradiol production (5 days GC culture spent media). Curcumin had shown a significantly higher PF survival rate (%), i.e. 74.3±1.5, 76.3±1.4 at 10 and 25 μM levels respectively. Similarly, higher PF growth rates (μm per day), i.e. 16.1±0.9 was observed at 50 μM levels. Similarly, curcumin was effective @ 50 μM level to increase the granulosa cell number as well as estradiol production with a mean granulosa cell number (×105) and estradiol production (pg) values of 1.55±0.04 and 85.3±3.3 respectively. Likewise, carbazole was effective at the level of 25 μM to increase the PF growth rate (μm per day), survival rate (%)with mean values of 74.3±1.3, 12.1±0.9. Similarly, carbazole was effective at 50 μM dose levels in the granulosa cell number increment (×105) with a mean value of 1.57±0.02. No significant change in estradiol production was observed in carbazole treated group.